We can see that the y-intercept of the line is [tex]-2[/tex] and its slope is [tex]-\frac{2}{3}\\[/tex] since to get from [tex](-3,0)[/tex] to [tex](0,-2)[/tex] we have to run by [tex]3[/tex] units to the right and rise by [tex]2[/tex] units down. The the equation of your line in slope-intercept form is [tex]y = -\frac{2}{3}x -2\\[/tex]. All we have to do now is to rewrite it in standard form.
[tex]y = -\frac{2}{3}x -2\\ 3(y) = (-\frac{2}{3}x -2)3 \\ 3y = -2x -6 \\ 2x +3y = -2x -6 +2x \\ 2x +3y = -6 [/tex]
Answer:
[tex]2x +3y = -6[/tex]